(untitled) (Research, Society and Development, 2023)
Objective: To describe part of the epidemiological profile comparing data on hospitalizations and deaths due to asthma in the State of Roraima-RR between the years 2018 to 2022 with data from the Department of Informatics of the Unified Health System (DATASUS). Methodology: This is a retrospective epidemiological descriptive study, based on secondary data, from the Hospital Information System (SIH), in DATASUS. Results: 667 hospital admissions for ’’Asthma’’ CID: (J45 and J46) were cataloged, considering public and private hospitals, and all categories of care. The color/race, predominantly pointed out was the ’’brown’’ and variable ’’no information’’. The genders evidenced in hospitalizations in these periods, stood out to the male gender. As for the age group, between 1 and 4 years, it adopted a higher number of hospitalizations, followed by the age group of 5 to 9 years. It was also presented, as a variable referring to the average length of stay of hospitalizations, the values ​​of hospital services, average values of hospitalizations. In the period surveyed, 05 deaths were recorded, with variables different from those described in the hospitalizations, such as the predominance of deaths to females and different age groups. Conclusion: Asthmatics should be assisted and monitored by Primary Health Care (PHC) teams. Asthma has no cure, but treatment aims to achieve and maintain control of the disease, with possible medication, and improve quality of life. It is noticed, the current gap of the health services regarding the prevention of a controllable pathology, as well as the need to foster the understanding of the epidemiological profile of the post-pandemic global emergency pathology.